2021
DOI: 10.3233/jad-210031
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas Gingivalis Infection Induces Synaptic Failure via Increased IL-1β Production in Leptomeningeal Cells

Abstract: Background: Studies have reported that synaptic failure occurs before the Alzheimer’s disease (AD) onset. The systemic Porphyromonas gingivalis (P. gingivalis) infection is involved in memory decline. We previously showed that leptomeningeal cells, covering the brain, activate glial cells by releasing IL-1β in response to systemic inflammation. Objective: In the present study, we focused on the impact of leptomeningeal cells on neurons during systemic P. gingivalis infection. Methods: The responses of leptomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This procedure has the advantage of remaining unbiased by factors such as experimenter manipulation, reflecting an augmentation of existing behavioral activity rather than inducing artificial changes in normal behavioral patterns, and using a high-intensity learning stimulus, which is particularly suitable for older mice (Liu et al, 2012). In this investigation, we uti- the role of P. gingivalis infection in synaptic failure (Huang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure has the advantage of remaining unbiased by factors such as experimenter manipulation, reflecting an augmentation of existing behavioral activity rather than inducing artificial changes in normal behavioral patterns, and using a high-intensity learning stimulus, which is particularly suitable for older mice (Liu et al, 2012). In this investigation, we uti- the role of P. gingivalis infection in synaptic failure (Huang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, the conditioned fear test revealed that the CP group demonstrated a reduced memory capacity, aligning with their diminished dendritic spine density. A parallel study indicated that systemic P. gingivalis infection elevated IL‐1 expression and reduced synaptophysin (SYP) expression in the proximal cortex of the leptomeninges in mice, suggesting the role of P. gingivalis infection in synaptic failure (Huang et al, 2021). In yet another study, oral Pg infection was seen to decrease PSD95 and SNAP25 expression in hippocampal and cortex regions in App KI mice (Hao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…They discovered that host genes interacting with Pg were significantly enriched in those associated with AD. In addition, mice or rats chronically infected with Pg orally exhibit Pg colonization in the hippocampal and cortical layers, accompanied by classic AD-like pathology such as neuroinflammation, neurodegeneration, Tau phosphorylation, and the formation of both intracellular and extracellular Aβ plaques and NFT ( Wu et al, 2017 ; Ilievski et al, 2018 ; Dominy et al, 2019 ; Díaz-Zúñiga et al, 2020 ; Haditsch et al, 2020 ; Huang et al, 2021 ; Sansores-España L. D. et al, 2021 ; Tang et al, 2021 ; Zeng et al, 2021 ; Hao et al, 2022 ).…”
Section: Periodontal Pathogens Potentially Associated With Admentioning
confidence: 99%
“…The NLRP3 inflammasome plays critical roles in various inflammatory disorders, including Alzheimer's disease, diabetes, and other inflammation-related diseases (18)(19)(20). It consists of an N-terminal PYD, a central NOD (also called the NACHT domain), and a C-terminal LRR domain (21).…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%